Ethical principles, challenges and opportunities when conducting genetic counselling for schizophrenia - Zingela, Zukiswa; Sokudela, Funeka; Thungana, Yanga; van Wyk, Stephan (Frontiers in Psychiatry, 2023)
Ethical challenges of genetic counselling for schizophrenia include effective communication of critical scientific information in an easily understood manner by patients and relatives, and the ability to ensure communication is unencumbered by medical jargon. Levels of literacy in the target population may limit this process, making it difficult for patients to attain the desired levels of informed consent to make crucial decisions during genetic counselling. Multilingualism in target communities may further complicate such communication. This paper outlines the ethical principles, challenges and opportunities facing clinicians when conducting genetic counselling for schizophrenia and how these might be met, drawing on lessons from South African studies. The paper draws on reflections of clinician and researcher experiences gained from clinical practice or research on the genetics of schizophrenia and psychotic disorders in South Africa. The context of genetic studies in schizophrenia is used to illustrate the ethical challenges in genetic counselling for schizophrenia, both in clinical and research settings. Attention is also drawn to multicultural and multilingual populations, particularly where the preferred language lacks a well-developed scientific language of communication for some of the genetic concepts that have to be presented during the genetic counselling process. The authors describe the ethical challenges and how to address these to empower patients and relatives to make well-informed decisions despite these obstacles. Principles applied by clinicians and researchers during the genetic counselling are described. Potential solutions, including the establishment of community advisory boards to address potential ethical challenges inherent to the genetic counselling process, are also shared. Genetic counselling for schizophrenia still faces ethical challenges which require a balance of principles of beneficence, autonomy, informed consent, confidentiality and distributive justice, while striving to present accuracy in the science that guides the process. Evolution in language and cultural competency therefore needs to occur alongside scientific advances in genetic research. Key stakeholders need to partner and build capacity and expertise in genetic counselling through the provision of funding and resources. The goal of partnerships is to empower patients, relatives, clinicians and researchers to share scientific information in a manner guided by empathy while retaining scientific accuracy.